2016
DOI: 10.1016/j.clinph.2015.04.062
|View full text |Cite
|
Sign up to set email alerts
|

Increased intracortical inhibition in elderly adults with anterior–posterior current flow: A TMS study

Abstract: Please cite this article as: Sale, M.V., Lavender, A.P., Opie, G.M., Nordstrom, M.A., Semmler, J.G., Increased intracortical inhibition in elderly adults with anterior-posterior current flow: a TMS study, Clinical Neurophysiology (2015), doi: http://dx.doi.org/10. 1016/j.clinph.2015.04.062 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesettin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…In this study, TMS intensities that correspond to RMT, AMT and 1 mV test stimulus were higher in older adults compared with young, indicating reduced corticomotor excitability with advancing age. Our findings are in line with previous studies which observed higher thresholds (Sale et al., ) and higher stimulus intensities required to elicit target MEP amplitudes (Pitcher et al., ) in older adults. This may, in part, be due to reduced excitability in the underlying neurons or an increased distance between the TMS coil and underlying neural tissue due to cortical atrophy with advancing age (Fjell et al., ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, TMS intensities that correspond to RMT, AMT and 1 mV test stimulus were higher in older adults compared with young, indicating reduced corticomotor excitability with advancing age. Our findings are in line with previous studies which observed higher thresholds (Sale et al., ) and higher stimulus intensities required to elicit target MEP amplitudes (Pitcher et al., ) in older adults. This may, in part, be due to reduced excitability in the underlying neurons or an increased distance between the TMS coil and underlying neural tissue due to cortical atrophy with advancing age (Fjell et al., ).…”
Section: Discussionsupporting
confidence: 94%
“…In young individuals, the magnitude of IHI was comparable when the test stimulus was induced with PA and AP current directions (Ghosh et al., ). However, age‐related comparisons may be more sensitive with AP stimulation compared with PA. For example, age‐related differences in intracortical inhibition that also suppresses later I‐waves much more so than early I‐waves (Di Lazzaro et al., ; Nakamura, Kitagawa, Kawaguchi, & Tsuji, ) was only evident with AP, but not PA stimulation (Sale, Lavender, Opie, Nordstrom, & Semmler, ). Therefore, assessing IHI with AP‐induced current may be required to detect age‐related effects.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature suggests contradictory effects of age on SICI and LICI during both relaxation [27,29,[49][50][51][52][53][54][55][56][57][58][59][60][61][62] and isometric muscle activation [30,33,63], with variations in methodology and subject characteristics likely contributing to this heterogeneity. Despite this, as the conditioning stimulus intensity was adjusted to produce 50% inhibition of the test MEP during postural contractions, our findings could not have been confounded by any age-related differences in inhibition at baseline.…”
Section: Age-related Differences In Gabaergic Inhibition During Movemmentioning
confidence: 99%
“…Nonetheless, the contribution of early and late I waves to the MEP are known to be altered when the target muscle is active [51], which may complicate the interpretation of the interactions between inhibitory circuits in active muscle. Furthermore, it is not known whether the composition of the descending volley is different in older adults, although recent evidence comparing MEP latencies between antero-posterior (preferential I3 wave activation) and posterior-anterior (preferential I1 wave activation) TMS showed similar recruitment of I waves in older adults [52]. Further research is therefore needed to confirm whether the descending volley (that produces similar MEP amplitudes) is comparable in young and old adults, particularly when the muscle is active.…”
Section: And Are Reduced In Individuals Withmentioning
confidence: 99%